A Nomogram of Lateral Abdominal Wall Fat Thickness in Normal Third Trimester Fetuses. Issue 1 (March 2019) - Dubinsky, Theodore J.; O'Regan, Jeremiah; Sonneborn, Rachelle; Hippe, Dan S.; Dighe, Manjiri; Moshiri, Mariam
Abstract: Objectives: The objective of this study is to establish a nomogram of fetal abdominal wall fat thickness in fetuses with known normal neonatal outcomes. Methods: After IRB approval (HSD-49496), 157 ultrasound examinations in 100 patients, 41 of whom had multiple examinations during the same pregnancy were reviewed. The thickness of the fetal lateral abdominal wall fat Interreader agreement was summarized using the intraclass correlation coefficient (ICC). Fat thickness growth curve equations were estimated to quantify the relationship between fat thickness and gestational age. Results: The abdominal wall fat had an intraclass correlation coefficient of 0.93 (95% confidence interval, 0.90–0.96) for 2 readers. Fat thickness increased in all 41 fetuses with multiple examinations ( P < 0.001). Fat thickness increased 0.19 mm per week on average (95% confidence interval, 0.17–0.21 mm; P < 0.001) from an average of 1.7 mm at 22 weeks and 4.3 mm at 36 weeks. Conclusions: Lateral wall abdominal fat can be reproducibly measured with good inter observer correlation, and fat does increase with increasing gestational age in normal fetuses. We believe the utility of fetal fat is the documentation of its presence as a reassuring finding indicative of normal fetal health, particularly when prior dating is discrepant or not available during the third trimester.